The lex mercatoria in theory and practice - Toth, Orsolya, 1981 February 26- (Oxford : Oxford University Press, 2017)
This title analyses the 'law merchant', clarifies current thinking and includes a formula to recognise and apply a rule of the lex mercatoria in practice.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 9, 2017).
Keywords: Law merchant; Commercial law; Law